2021
DOI: 10.3390/antibiotics11010001
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antibiotic Resistance of Salmonella Serotypes and Whole-Genome Sequencing of Multiresistant Strains Isolated from Food Products in Russia

Abstract: Food products may be a source of Salmonella, one of the main causal agents of food poisoning, especially after the emergence of strains resistant to antimicrobial preparations. The present work dealt with investigation of the occurrence of resistance to antimicrobial preparations among S. enterica strains isolated from food. The isolates belonged to 11 serovars, among which Infantis (28%), Enteritidis (19%), and Typhimurium (13.4%) predominated. The isolates were most commonly resistant to trimethoprim/sulfame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 86 publications
2
6
1
Order By: Relevance
“…Nevertheless, the presence of three IncFIB plasmids and one IncX1 plasmid found among the isolates that carried several AMR genes was particularly worrisome, as they increase the risk of spreading multiple resistance genes. Although the AMR genes (TEM-1, AAC(3)-IV, APH(4)-Ia, and floR) carried by the IncX1 plasmid in this study were completely different from those reported in previous work (repA, qnrS1, tet(A), cmlA1, sul3, and bla TEM-1B genes) [48][49][50], the current observations could be well-explained by prior research showing that isolates originating from different countries belonging to different lineages may be exposed to different environments and therefore carry different resistance genes [51]. On the other hand, all isolates carried an IncFIB plasmid that could increase colonization in the chicken cecum, which may help to explain its persistence in the food animal population [52].…”
Section: Discussioncontrasting
confidence: 96%
“…Nevertheless, the presence of three IncFIB plasmids and one IncX1 plasmid found among the isolates that carried several AMR genes was particularly worrisome, as they increase the risk of spreading multiple resistance genes. Although the AMR genes (TEM-1, AAC(3)-IV, APH(4)-Ia, and floR) carried by the IncX1 plasmid in this study were completely different from those reported in previous work (repA, qnrS1, tet(A), cmlA1, sul3, and bla TEM-1B genes) [48][49][50], the current observations could be well-explained by prior research showing that isolates originating from different countries belonging to different lineages may be exposed to different environments and therefore carry different resistance genes [51]. On the other hand, all isolates carried an IncFIB plasmid that could increase colonization in the chicken cecum, which may help to explain its persistence in the food animal population [52].…”
Section: Discussioncontrasting
confidence: 96%
“…Salmonellosis is the second most common gastrointestinal infection in humans after campylobacteriosis in the European Union [ 4 ] and is even a leading reported foodborne illness in some parts of the USA [ 5 ]. In the Russian Federation, salmonellosis remains an important cause of foodborne outbreaks, being third in the incidence among infections with a fecal–oral transmission mechanism [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the increasing incidence of AR of Salmonellosis may result from misusing these antibiotics in veterinary fields (Economou and Gousia, 2015). Rakitin et al (2022) investigated the incidence of antimicrobial resistance among salmonella enterica strains obtained from food; their findings indicated that MDR against routinely used antibiotics as most of the strains (68.75%) exhibited multiple AR against the most commonly used antibiotics. The rise of MDR Salmonella strains is a worldwide public health concern.…”
Section: Discussionmentioning
confidence: 99%